Microcavity enhanced single photon emission from two-dimensional WSe2 - Flatten, L; Weng, L; Branny, A; Johnson, S; Dolan, P; Trichet, A; Gerardot, B; Smith, J (American Institute of Physics Publishing, 2018)
Atomically flat semiconducting materials such as monolayer WSe2 hold great promise for novel optoelectronic devices. Recently, quantum light emission has been observed from bound excitons in exfoliated WSe2. As part of developing optoelectronic devices, the control of the radiative properties of such emitters is an important step. Here, we report the coupling of a bound exciton in WSe2 to open microcavities. We use a range of radii of curvature in the plano-concave cavity geometry with mode volumes in the λ3 regime, giving Purcell factors of up to 8 while increasing the photon flux five-fold. Additionally, we determine the quantum efficiency of the single photon emitter to be η=0.46±0.03. Our findings pave the way to cavity-enhanced monolayer based single photon sources for a wide range of applications in nanophotonics and quantum information technologies.